Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21203/rs.3.rs-1991437/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Willingness to Pay for Social Health Insurance and Its Determinants Among Public School Teachers in Akaki Kality Sub-City of Addis Ababa City Administration: Ethiopia. Institution-based cross-sectional study

Abstract: Background: Ethiopia is one of the countries with high out-of-pocket payments leading to catastrophic health expenditure. The government of Ethiopia introduced social health insurance scheme to reduce the out-of-pocket payments. However, there is limited evidence on willingness to pay for social health insurance among formal sector employees in the country. This study aimed to assess the willingness to pay for social health insurance and its associated factors among teachers in public school of Addis Ababa. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…The WTP for SHI was found to be influenced by sociodemographic factors like education level ( 20 22 , 25 , 31 , 32 ), income ( 17 , 19 21 , 27 , 28 , 31 , 34 ), age ( 26 , 28 , 31 ), marital status ( 28 , 33 ), occupation or job description ( 28 ), family size ( 29 , 30 , 34 ), and job experience ( 16 ); health and illness status such as self-rated healthiness ( 16 ), the presence of acute ( 20 , 21 , 31 ), and chronic illnesses ( 34 ); health service related factors like previous medical bills ( 16 , 18 , 21 , 22 , 24 , 27 , 28 , 30 , 35 ), referral system ( 26 ), regular medical checkup ( 26 ), and health service quality ( 16 , 19 , 24 – 27 ); awareness or knowledge ( 16 18 , 20 23 , 27 , 29 , 30 , 32 , 34 , 35 ); perception ( 24 , 31 ); attitude ( 17 , 21 , 27 , 33 , 34 ); and factors related to the scheme such as trust ( 17 , 23 ), premium amount ( 19 ), and the scope of the benefit packages ( …”
Section: Resultsmentioning
confidence: 99%
“…The WTP for SHI was found to be influenced by sociodemographic factors like education level ( 20 22 , 25 , 31 , 32 ), income ( 17 , 19 21 , 27 , 28 , 31 , 34 ), age ( 26 , 28 , 31 ), marital status ( 28 , 33 ), occupation or job description ( 28 ), family size ( 29 , 30 , 34 ), and job experience ( 16 ); health and illness status such as self-rated healthiness ( 16 ), the presence of acute ( 20 , 21 , 31 ), and chronic illnesses ( 34 ); health service related factors like previous medical bills ( 16 , 18 , 21 , 22 , 24 , 27 , 28 , 30 , 35 ), referral system ( 26 ), regular medical checkup ( 26 ), and health service quality ( 16 , 19 , 24 – 27 ); awareness or knowledge ( 16 18 , 20 23 , 27 , 29 , 30 , 32 , 34 , 35 ); perception ( 24 , 31 ); attitude ( 17 , 21 , 27 , 33 , 34 ); and factors related to the scheme such as trust ( 17 , 23 ), premium amount ( 19 ), and the scope of the benefit packages ( …”
Section: Resultsmentioning
confidence: 99%
“…For instance, in Mekelle, the largest city in the country's Tigray region, a majority (85%) of the 381 public servants were willing to be part of the social health insurance scheme, with a mean WTP of 3.6% of their monthly salary [18]. Although not as high as in Mekelle, surveys amongst teachers in Harar, Wolaita Sodo, Gondar and Akaki Kality (a sub-city of Addis Ababa), yielded WTP rates of between 62% and 74% [19][20][21][22]. A meta-analysis covering 18 studies showed that, on average, about 42% of formal sector workers are WTP for SHI [23].…”
Section: Introductionmentioning
confidence: 99%